The relationship between disease prognosis and serum calcium and corrected calcium levels in COVID-19 patients - Ekinci, Iskender; Özkan, Hanişe; Büyükkaba, Mitat; Kirac Utku, İrem and Çınar, Ahmet and Güven, Ramazan and Akarsu, Murat and Kumbasar, Abdulbaki and Uzun, Hafize and Tabak, Ömür (The European Research Journal, 2021)
Objectives: The present study aimed to evaluate whether low serum calcium (Ca) and corrected calcium (cCa) levels could predict disease prognosis and mortality in patients with COVID-19. Methods: In this study, we retrospectively enrolled 206 eligible patients with COVID-19, diagnosed at Turkey Kanuni Sultan Süleyman Training and Research Hospital between March 12, 2020 and June 15, 2020. Results: Serum Ca level was 8.8 ± 0.57 mg/dL and the serum cCa level was 8.99 ± 0.53 in all patients. The patients were divided into two groups, such as hypocalcemic and non-hypocalcemic patients. We observed that serum Ca levels of patients who died were significantly lower than that of surviving patients. A significant negative correlation was found between serum cCa level and albumin level. A significant positive correlation was found between serum cCa level and C-reactive protein, lactate dehydrogenase, ferritin, procalcitonin, troponin, CURB-65 score, and quick Sepsis-related Organ Failure Assessment (q-SOFA) score. Univariate logistic regression analysis revealed that age, respiratory rate, saturation, heart rate, lymphocyte, serum calcium, D-dimer, CURB-65 score, and q-SOFA score were independent predictors of high-risk group of mortality. Conclusions: This study confirms that the severity of COVID-19 is associated with lower concentrations of serum Ca. The cCa levels were associated with certain prognostic factors. Serum Ca and cCa levels could be an early and helpful marker to improve management of patients with COVID-19. We recommend evaluation of calcium in patients on initial presentation and serial monitoring during hospitalization in order to perform timely and appropriate corrective actions.